Life cycle assessment of ceramic tiles. Environmental and statistical analysis. - Ibañez-Fores, Valeria (The International Journal of Life Cycle Assessment)
Purpose The aim of this paper is to conduct a life cycle assessment study of ceramic tiles (single-fired glazed stoneware) in order to identify the stages that produce the greatest impact on the environment and the materials and/or processes that make the largest contribution to that impact. The life cycle is considered to be made up of seven stages : (1) mining the clay, (2) atomising the clay, (3) production of frits and glazes, (4) production of ceramic tiles, (5) distribution, (6) installatio and usage, and, on ending their useful life (7) treatment as construction and demolition waste. Materials and methods A specific life cycle inventory was developed taking 1 m2 of ceramic tile over a period of 20 years as the functional unit and using annual data gathered directly from 35 Spanish enterprises involved in the different stages of the life cycle of ceramic tiles. This inventory was then used to obtain environmental indicators (global warming, ozone layer depletion, acidification, eutrophication, photochemical oxidation and human toxicity) for each enterprise and each stage of the life cycle under study. Results and discussion. Environmental data were submitted to a statistical analysis. This analysis made it possible to model the distribution of environmental behaviour of the life cycle of ceramic tiles considering the different influences from the different companies that were consulted for each stage in the life cycle. The statistical study allowed also obtaining confidence intervals for the mean and standard deviation of the environmental results obtained for each impact category. Conclusions The stage of the life cycle with the greatest environmental impact for all the impact categories is the manufacture of the tile, followed by the process of atomising the clay and the distribution of the product. There is a direct correlation between these findings and the high level of energy consumption (mainly natural gas and fuel) in these stages. Moreover, the statistical analysis provided 95 percent level of confidence intervals for the mean and the standard deviation very accurate which shows that using the mean inventory values from all enterprises that were consulted with the same stage of the life cycle is a suitable method of working. Future users of the inventory may use the probability distributions obtained for calculating percentiles or other measures to assess their data.